High positive supercoiling in vitro catalyzed by an ATP and polyethylene glycol-stimulated topoisomerase from Sulfolobus acidocaldarius. - Forterre, P (1985)
A topoisomerase able to introduce positive supercoils in a closed circular DNA, has been isolated from the archaebacterium Sulfolobus acidocaldarius. This enzyme, fully active at 75 degrees C, performed in vitro positive supercoiling either from negatively supercoiled, or from relaxed DNA in a catalytic reaction. In the presence of polyethylene glycol (PEG 6000), this reaction became very fast and highly processive, and the product was positively supercoiled DNA with a high superhelical density (form I+). Very low (5 - 10 micromoles) ATP concentrations were sufficient to support full supercoiling; the nonhydrolyzable analogue adenosine-5' -0-(3-thiotriphosphate) also sustained the production of positive supercoils, but to a lesser extent, suggesting that ATP hydrolysis was necessary for efficient activity. Nevertheless, low residual of positive supercoiling occurred, even in the absence of ATP, when the substrate was negatively supercoiled. Finally, the different ATP-driven topoisomerizations observed, i.e., relaxation of negative supercoils and positive supercoiling, in all cases increased the linking number of DNA in steps of 1, suggesting the action of a type I, rather than a type II topoisomerase.=